EDITORIAL - Rocha Machado, Bianca; Campo Dall'Orto Corrêa, Elisa; Carreiro Cruz, Francisco Edson; Cavalcante Brígido, Anúzia Gabrielle; de Carvalho Pagliaro, Heitor; Ferreira Medeiros, Kelvlin; Noleto Ferreira, Lennon Pedro; Möller, Mathias Alberto; Gonçalves Fernandes, Mayã; dos Santos Sandoval, Rafael Antonio; Santos dos Prazeres, Rogério; Martins Mendes, Ruth de Paula; et al. (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2014)
Editorial do volume 03, número 15, ano 2014.